Shadows of Fate: A Refugee Childhood - Gluth, Susan (Germany, 2006)
Verzio FF submission The girls are 11 and 12 years old. They are friends. Having escaped the massacres in their homeland together with the other surviving members of their families, they have reached the safety of Bredjing refugee camp in the south-east of the neighbouring country of Chad. "Thanks be to Allah – we had everything!" says Jasmin’s mother when she speaks of the good times in their native land before the war broke out. We witness with our own eyes what is left for her and the other families. What happened to them in between we learn from the stories they tell. The shadows of the past are their constant companions; the uncertainty of the future hovers over their daily lives as they wait in the camp. The film approaches the two girls tactfully and with sensitivity. It shows their daily lives, which in spite of the poverty and hardship rise above what has happened and what they have experienced with bright moments and dignity, with games and songs and school lessons and the strength of their Muslim faith. And yet the tragedy is ever-present, lurking just beneath the surface.